미토콘드리아 산소호흡 측정방법 - 허준원; 조은정; 최영주; 서대윤; 한진; 박동호; 강주희; 곽효범 (Exercise science (Seoul, Korea), 2023)
PURPOSE: With the widespread of mitochondrial function, the need to accurately quantify and comprehend mitochondrial O2 respiration has gained prominence within the physiological and pathological spheres. Various in situ, in vitro, and in vivo approaches have been available to investigate numerous aspects of mitochondrial O2 consumption. This review aims to provide a specific method for researchers to consider in examining mitochondrial O2 respiration using permeabilized or homogenized tissues. These techniques allow direct access to mitochondrial O2 respiration, facilitating an exploration of mitochondrial bioenergetics under well-defined substrate conditions. METHODS: Here, we present a method for measuring mitochondrial O2 consumption in permeabilized or homogenized tissues using high-resolution respirometry (Oroboros Oxygraph-2K, Oroboros Instrument). RESULTS: A high-resolution respirometry provides the most direct way to assess mitochondrial O2 respiration with interpretations based on specific modeling approaches. CONCLUSIONS: As many diseases are closely associated with mitochondrial dysfunction, ongoing advancements in this methodology may provide researchers with exciting and novel opportunities for finding the potential role of mitochondria in the etiology and treatment of various diseases KCI Citation Count: 0